Anatomy of a Rhetorical Gesture (Per Musi, 2018)
The article analyzes a rhetoric gesture that frequently appears in tonal and post tonal repertoires, and starting from an analysis by Patrick McCreless (2006) postulates that the gesture is more limited than what the author proposes in this reference, reducing it to three stages related with the process of expectations. For the analysis, it checks the definitions offered by renowned investigators of gesture in general and rhetoric gesture in particular. The analysis is based in concepts that imply: the participation of the body in the musical audition, the attributes of significances, the metaphoric audition and, finally, the model of expectations proposed recently by David Huron. Finally, it analyses the instances of the gesture that appear in the pianistic and symphonic repertoire from the eighteenth century up to the beginning of the twentieth century.